A estética da ruína como poética - Bruno de Guimaraens Amarante (2013)
The following dissertation is the fruit of the conceptual, aesthetic and interpretative relationships between my artistic production and the object of research: the aesthetic of ruins as a poetic. To this end, I observed different aspects of the imagery of the ruin where the poetic and plastic potentials in the productions of others and in agent images made it possible to find correlations with my work.This research permeates the chronological time of the visual arts, relativizing the works of different artists, of different times and media that contained, or still contain, the imagery of the ruin in their works. This research proposes an analysis that comprises the ruinous poetic, whether by Piranesi, Anselm Kiefer, or Claudi Casanovas, relativizingits sensory faculties. These faculties have incidence both on mnemonic questions and on issues dealing with the passage of time, be it urban, human or geologicsublime. Also it is the target of my observations some images of my city and its surroundings, in which the visuality of the ruin has some peculiarities.The interpretation proposed in this work is based on the particular thought of the author about the object image. It is also based on an understanding of the thoughts of the selected artists, historians and philosophers. These thoughts, inasmuch as they are a reflection of the same object, and the discussed agent images coexist in my mnemonicinventory, with an active influence in the reflections and poetic journey of my own plastic and textual production.